Revision of the Protocol of the Telephone Triage System in Tokyo, Japan - Atsushi Sakurai; Jun Oda; Takashi Muguruma; Shiei Kim; Sachiko Ohta; Takeru Abe; Naoto Morimura (Emergency Medicine International)
Introduction. The Emergency Telephone Consultation Center in Tokyo (#7119) was the first telephone triage system in Japan and has operated since 2007. This study examined the revision of the #7119 protocol by referring the linked data to each code of the triage protocol. Methods. We selected candidates based on the medical codes targeted by the revision, linking data from the nurses’ decisions in triage and the patients’ condition severity when the ambulance arrived at the hospital, gathering data from June 1, 2016, to December 31, 2017. Then, several emergency physicians evaluated the cases and decided whether the code should be moved to the more or less urgent category or if new protocols and codes would be established. Results. In this revision, 371 codes were moved to the less urgent category, 35 codes were moved to the more urgent category, and 128 codes were newly established. In all, 59 red codes (transfer to the ambulance dispatcher) were reduced, while 254 orange codes (attendance at hospital within 1 hour) and yellow codes (within 6 hours) were moved to less urgent, and 12 yellow and green codes (within 24 hours) were moved to more urgent. Conclusion. We adjusted the triage codes for the revision by linking the call data with the case data. This revision should decrease the inappropriate use of ambulances and reduce the primary care workload. To achieve a more accurate revision, we need to refine the process of evaluating the validity of patients’ acuity over the telephone during triage.